2016
DOI: 10.1016/j.celrep.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of RBFOX2 Is an Early Event in Cardiac Pathogenesis of Diabetes

Abstract: Alternative splicing (AS) defects that adversely affect gene expression and function have been identified in diabetic hearts; however, the mechanisms responsible are largely unknown. Here we show that the RNA-binding protein RBFOX2 contributes to transcriptome changes under diabetic conditions. RBFOX2 controls AS of genes with important roles in heart function relevant to diabetic cardiomyopathy. RBFOX2 protein levels are elevated in diabetic hearts despite low RBFOX2 AS activity. A dominant negative (DN) isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(117 citation statements)
references
References 46 publications
7
106
0
Order By: Relevance
“…Finally, misregulation or misexpression of both CELF2 and RBFOX2 have been implicated as contributors to human disease including cancer, muscular dystrophies, heart failure, and Type 1 diabetes (Kuyumcu-Martinez et al 2007;Cooper et al 2009;Verma et al 2013;Nutter et al 2016). Our finding of mutual antagonism between these proteins suggests that disease-relevant splicing attributed previously to CELF2 or RBFOX2 may also be impacted by altered expression of the other.…”
Section: Implications Of Celf2/rbfox2 Antagonism For Understanding Humentioning
confidence: 54%
See 1 more Smart Citation
“…Finally, misregulation or misexpression of both CELF2 and RBFOX2 have been implicated as contributors to human disease including cancer, muscular dystrophies, heart failure, and Type 1 diabetes (Kuyumcu-Martinez et al 2007;Cooper et al 2009;Verma et al 2013;Nutter et al 2016). Our finding of mutual antagonism between these proteins suggests that disease-relevant splicing attributed previously to CELF2 or RBFOX2 may also be impacted by altered expression of the other.…”
Section: Implications Of Celf2/rbfox2 Antagonism For Understanding Humentioning
confidence: 54%
“…5E). RBFOX2 has been shown to be dysregulated in the hearts of diabetic patients and a mouse model of Type I diabetes (T1D), where it forms a dominant negative version of the protein, leading to a number of splicing changes (Nutter et al 2016). CELF1 has also been shown to be up-regulated in diabetic hearts via PKC signaling (Kuyumcu- Martinez et al 2007;Verma et al 2013), but the global consequences of this have not been examined.…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…Diabetes also impacts skeletal muscle function causing muscle weakness and atrophy (Andersen et al, 1997;Hernandez-Ochoa & Vanegas, 2015) RBPs are important regulators of cell survival and function, because they have essential roles in fundamental cellular processes such as proliferation, differentiation, and apoptosis (Brinegar & Cooper, 2016;Castello, Fischer, Hentze, & Preiss, 2013;Gerstberger et al, 2014). Dysregulation of RBPs has been observed in a plethora of diseases including cancer (reviewed in Castello et al, 2013;Gerstberger et al, 2014), neurological (reviewed in Cookson, 2017;Donlin-Asp, Rossoll, & Bassell, 2017), and cardiovascular diseases (reviewed in de Bruin, Rabelink, van Zonneveld, & van der Veer, 2017;Nutter et al, 2016;Verma et al, 2016;Xin, Deng, & Fu, 2014). Several RBPs have been associated with the development of diabetes or with diabetic complications (Ben-Haim, Moshitch-Moshkovitz, & Rechavi, 2015;Chu et al, 2008;Gerken et al, 2007;Lyssenko et al, 2008;Rao et al, 2016;Scott et al, 2007;van Hoek et al, 2008;Wood et al, 2016).…”
Section: Rna-binding Proteinsmentioning
confidence: 99%
“…Nutter et al [23] recently suggested that high concentration of a protein RBFOX2 in cardiac cells can interfere with many important molecular mechanisms. In consequence, leading to inappropriate protein and calcium exchange in cardiomyocytes.…”
Section: New Reports On Pathogenesis Of Diabetic Cardiomyopathymentioning
confidence: 99%